Extreme Weather and Inter-State Migration in India - Richa Richa; Ilan Noy; Subir Sen (Center for Economic Studies and ifo Institute (CESifo), 2024)
Extreme weather induced migration is a growing concern for low and middle income countries due to the increased variability in the weather and the increase in the number of extreme weather disasters associated with climate change. The objective of this paper is to examine the inter-linkages between weather, disasters, and migration, in India. To examine the bidirectional flow of migrants across Indian states, we estimate gravity models with Poisson Pseudo Maximum Likelihood (PPML), in line with previous studies' methodology. We find that agriculture-dependent states and states with low level of human development are more likely to face out-migration driven by weather variations and disasters. Internal migration is seasonal, temporary and often short-distance in nature. We find statistical evidence that repeated exposure of vulnerable populations to extreme weather and disasters may ultimately lead to more permanent migration. This raises urgent questions concerning the efficacy of disaster risk management and climate change adaptation policies at the sub-national level.
Keywords: O15; Q54; 330; climate; disasters; bilateral migration; NELM; gravity model